To analyze the equation \(-12 (x-3) - 52 = -16\), we begin by simplifying it step by step.
-
Distribute the \(-12\) across \((x - 3)\): \[ -12(x - 3) = -12x + 36 \] Therefore, the equation becomes: \[ -12x + 36 - 52 = -16 \]
-
Now combine the constants on the left side: \[ 36 - 52 = -16 \] So: \[ -12x - 16 = -16 \]
-
Next, add \(16\) to both sides to isolate the term with \(x\): \[ -12x = -16 + 16 \] Which simplifies to: \[ -12x = 0 \]
-
Finally, divide both sides by \(-12\): \[ x = 0 \]
Since we found a specific value for \(x\) (which is \(x = 0\)), we conclude that the equation has one solution.
In summary, the equation \(-12 (x-3) - 52 = -16\) has one solution, which is \(x = 0\).